Ochrona pracy dzieci i młodocianych w Republice Federalnej Niemiec: [Protection of work of children and young audults in the Federal Republic of Germany] (Studia Prawnicze / The Legal Studies, 2023)
This article presents provisions of the law of 1976 on protection of work of the young now binding in the Federal Republic of Germany. Studying the contents of this law the Author is of the opinion that it suits the interests of working youth. Violations of the provisions of this law are punished with penal sanctions. On the basis of data gathered from reports of administrative organs supervising employers as far as conformity with provisions of the law is concerned, and on the basis of results of empirical studies the Author comes to the conclusion that the law of 1976 is very often violated and that this happens in small workplaces more often than in bigger ones. Such violations are generally kept secret by young employees who often do not know the rights they have. Violations of the law are only divulged during the inspections by organs of state administration which in such cases impose rather mild penalties on the employers.Discussing the reasons of violating legal provisions in practice the Author points out to two elements, main ones according to his opinion. First, that the idea of protecting the work of the young contradicts the principles of the economic system aimed at gaining maximum productive effect. Second, that the structure of the relationship in a workplace, and especially in a small one,  does not encourage a young employee to seek protection of his rights: at the beginning a young man is more interested in speedy integration with the workplace and not in conflicting with it.